Patient public involvement (PPI) in health literacy research: Engagement of adults with literacy needs in the co‐creation of a hospital‐based health literacy plan - Verna B. McKenna; Jane Sixsmith; Niki Byrne (Wiley, 2023)
Abstract Background People with literacy needs can experience many challenges in accessing, understanding and using health services and health information. Such challenges can adversely impact patient‐provider interactions and ultimately, health outcomes. Healthcare providers need to be aware of health literacy (HL) to address the demands of healthcare systems, improve their interactions with communities and patients and promote patient engagement for improved health outcomes. Methods This paper reports on a process of patient and public involvement (PPI) with participants in an adult literacy programme acting as PPI contributors to identify priority areas for a local hospital HL action plan and to develop a protocol for a PPI process with other groups. A qualitative community‐based participatory research study design informed by principles of PPI was undertaken, drawing on the tools of participatory and visual methods, open discussion and workshop format to facilitate a process of co‐creation. Three workshops with six PPI contributors took place to identify issues to be included in the hospital action plan. PPI contributors identified issues and grouped these into priority areas using discussion and ranking procedures. Results Key areas prioritised for HL action by the PPI contributors were: verbal communication, emphasising the patient's right to understand, and improved understanding of medication use. These were incorporated into the action plan. The workshop format and process were deemed acceptable to the group and input on improvements will be incorporated into further work in this area. Conclusion PPI acts as a lever in the knowledge translation process. Genuine engagement with service users can meaningfully contribute to relevant and sustainable changes to services as well as foster the empowerment of service users. Patient or Public Contribution Members of the public with literacy needs actively participated in the co‐creation of a HL action plan for a local hospital and in the development of a protocol for a patient and public process for HL research.